2016
DOI: 10.1007/s12035-016-9741-5
|View full text |Cite
|
Sign up to set email alerts
|

Lower Serum Zinc and Higher CRP Strongly Predict Prenatal Depression and Physio-somatic Symptoms, Which All Together Predict Postnatal Depressive Symptoms

Abstract: Pregnancy and delivery are associated with activation of immune-inflammatory pathways which may prime parturients to develop postnatal depression. There are, however, few data on the associations between immune-inflammatory pathways and prenatal depression and physio-somatic symptoms. This study examined the associations between serum zinc, C-reactive protein (CRP), and haptoglobin at the end of term and prenatal physio-somatic symptoms (fatigue, back pain, muscle pain, dyspepsia, obstipation) and prenatal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 76 publications
3
44
0
6
Order By: Relevance
“…Several studies have noted that it is difficult to determine the mechanisms underlying perinatal psychiatric illness (Di Florio & Meltzer-Brody, 2015;Jones, Cantwell, & Psychiatrists, 2010). However, other studies have suggested that prenatal depression and physio-somatic symptoms have an immune-inflammatory pathophysiology (Roomruangwong, Kanchanatawan, Sirivichayakul, Mahieu, et al, 2017). For instance serum zinc is negatively associated with prenatal depression and physio-somatic symptoms, whereas C-reactive protein (CRP) is positively associated.…”
Section: Heterogeneity Of Clinical Phenotypes Of Perinatal Depressimentioning
confidence: 99%
“…Several studies have noted that it is difficult to determine the mechanisms underlying perinatal psychiatric illness (Di Florio & Meltzer-Brody, 2015;Jones, Cantwell, & Psychiatrists, 2010). However, other studies have suggested that prenatal depression and physio-somatic symptoms have an immune-inflammatory pathophysiology (Roomruangwong, Kanchanatawan, Sirivichayakul, Mahieu, et al, 2017). For instance serum zinc is negatively associated with prenatal depression and physio-somatic symptoms, whereas C-reactive protein (CRP) is positively associated.…”
Section: Heterogeneity Of Clinical Phenotypes Of Perinatal Depressimentioning
confidence: 99%
“…In addition, in women, body image satisfaction, which is associated with depressive and anxiety features, is strongly associated with activation of the TRYCAT pathway and especially with an index of quinolinic availability to the brain [99]. At the end of term pregnancy, TRYCAT pathway activity appears to be regulated by a complex network comprising inflammatory signals, nitrosative stress, bacterial translocation and regulatory autoimmune responses, pathways that are all associated with anxiety and depressive symptoms [93,100,101,102]. Overall, these studies indicate that aberrations in the TRYCAT pathway in pregnant females and parturients may be associated with increased anxiety and that sex, the menstrual cycle and PMS may have a profound effect on the TRYCAT pathway.…”
Section: Sex Anxiety and The Trycat Pathwaymentioning
confidence: 99%
“…There is now evidence that perinatal depression and anxiety symptoms are predicted by immune activation and inflammatory responses, including lowered tryptophan availability and endogenous compounds with anti-inflammatory and antioxidant properties (Maes et al, 1992(Maes et al, , 2000(Maes et al, , 2001, e.g. CC16 (Maes et al, 1999), T3 popyunsaturated fatty acids (PUFAs) (De Vriese et al, 2003) and zinc, increased inflammatory cytokines and CRP levels Maes, 2014, 2016;Leff-Gelman et al, 2016;Roomruangwong et al, 2016aRoomruangwong et al, , 2016c. Recently, we published that an increased hematocrit (Hct), but not mean corpuscular volume (MCV), at the end of term may predict postnatal depressive symptoms (Roomruangwong et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%